1991
DOI: 10.1002/elps.1150120703
|View full text |Cite
|
Sign up to set email alerts
|

The simplified technique of high resolution two‐dimensional polyacrylamide gel electrophoresis: Biomedical applications in health and disease

Abstract: The application of our simplified technique of high resolution two-dimensional polyacrylamide gel electrophoresis (2-D PAGE) to human body fluids is reviewed. Serum/plasma protein changes associated with alcohol abuse, familial dyslipoproteinemia ("fish-eye" disease), and myocardial infarction are demonstrated. High resolution 2-D PAGE of amniotic fluid, cerebrospinal fluid, urine, and saliva is shown with reference to the work of others, and the detection of pink-violet staining "lumicarmines" in sweat and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
2

Year Published

1992
1992
2003
2003

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 77 publications
0
16
0
2
Order By: Relevance
“…We have now addressed complications that arise from the presence of multiple components in an apparent single electrophoretic band by achieving better resolution of the protein mixture through the use of two-dimensional electrophoresis (2-DE). Application of 2-DE has only been reported in a few investigations on proteins in WS (35)(36)(37), and none so far on proteins found in in vivo formed EP. In none of these EP studies were proteins identified using MS techniques.…”
mentioning
confidence: 99%
“…We have now addressed complications that arise from the presence of multiple components in an apparent single electrophoretic band by achieving better resolution of the protein mixture through the use of two-dimensional electrophoresis (2-DE). Application of 2-DE has only been reported in a few investigations on proteins in WS (35)(36)(37), and none so far on proteins found in in vivo formed EP. In none of these EP studies were proteins identified using MS techniques.…”
mentioning
confidence: 99%
“…The samples were denatured (Section 2.5) and analysed (100 mg for CBB staining or 2.5 mg for silver staining) by isoelectric focusing (IEF, first dimension) in 5% w/v polyacrylamide gel rods (65 mm´3 mm diameter) containing 9 M urea, 0.5% Nonidet P-40 and 2% carrier ampholytes (Pharmalyte, pH 2.5±5.0; Ampholine, pH 5.0±7.0; Pharmalyte 2-D, pH 3±10; 2:3:6, v/v/v) followed by SDS-PAGE in 6±20% w/v polyacrylamide linear gradient gels (75´75 3 mm) at 40 mA/gel for 2 h in precooled (5 o C) 0.025 M Tris, 0.2 M glycine containing 0.1% w/v SDS [32]. For Multiphor 2-DE using immobilised pH gradients (IPGs) [33], 90 mg of urea was added to a mixture of 100 mL of saliva (diluted in 0.15 M sodium chloride; see Section 2.5), 4 mL of 2-mercaptoethanol, 4 mL of Pharmalyte pH 3±10, 4 mL of 25% v/v Triton X-100 and 2 mL of 0.2% w/v bromophenol blue*.…”
Section: -Dementioning
confidence: 99%
“…The gels were fixed overnight in methanol/acetic acid/ water (50:10:40, v/v/v) and stained in either (i) CBB R-250 (0.1% w/v Serva Blue R for 1 h at 60 o C) [32], or (ii) silver methylamine [34]. The Multiphor 2-DE gels were silver stained using the PlusOne kit as recommended by the manufacturer (Pharmacia Biotech).…”
Section: Stainingmentioning
confidence: 99%
“…The pooled samples (n = 4) were prepared for electrophoresis as described above (Section 2.3) and analysed (40 mg for CBB staining or 2.5 mg for silver staining) by IEF (first dimension) followed by SDS-PAGE (second dimension) [15]. Briefly, IEF in 5% w/v polyacrylamide gel rods (65´3 mm diameter) containing 9 M urea, 0.5% Nonidet P-40 and 2% carrier ampholytes (Pharmalyte pH 2.5±5.0, Ampholine pH 5.0±7.0, Pharmalyte 2-D pH 3± 10; 2:3:6 v/v/v) was followed by SDS-PAGE in 6±20% w/v polyacrylamide linear gradient gels (75´75´3 mm) at 40 mA/gel for 2 h in a Pharmacia GE 2/4 LS electrophoresis system using precooled (5 o C, MultiTemp) electrophoresis buffer (0.025 M Tris, 0.2 M glycine containing 0.1% w/v SDS) [15].…”
Section: -Dementioning
confidence: 99%
“…The gels were fixed overnight in methanol/acetic acid/ water (50:10:40, v/v/v) and stained in either (i) CBB (0.1% w/v Serva Blue R for 1 h at 60 o C) [15], or (ii) silver methylamine [16].…”
Section: Stainingmentioning
confidence: 99%